TEACHER’S PROFESSIONALISM – AN IMPORTANT RESOURCE TO INCREASE THE QUALITY OF TRAINING OF COMPETITIVE SPECIALISTS - KONDRASHOV, Nikolai; KONDRASHOVA, Lidiya (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2020)
The article is devoted to the problem of improving the quality of university education. The search for effective means of improving the preparation of students for professional activity has actualized the need to attract previously unused resources, to which the professional image of a university teacher has been attributed. Based on the study of theoretical sources, it has been established that the Professionalism of a teacher is not limited to a set of hotel professional properties and qualities that ensure a positive impact of a teacher on students. Professionalism as a complex personal education, combines in its content the structural components: motivational, cognitive, communicative, emotionalvolitional and reflective. Criteria and indicators of the level of formation of the professional image of the teacher are complex characteristics that include the requirements for the personality of a modern teacher, corresponding to the specifics of professional and educational activities and ensure the realization of the humanistic paradigm of the goal of modern education. At the initial stage of the study, the ideas of master students about the influence of the teacher’s personality on the educational process and the quality of professional training in the university education system were studied. The basis of the experimental work was the workshop "The Professionalism of the teacher is an important resource for the quality of training future specialists." In the course of the experimental study, positive dynamics of the levels of formation of the professionalism of teachers and levels of students training were noted. The results obtained confirmed the hypothesis that the professional image of the teacher is an important resource of the educational process and has a positive effect on improving the quality of university education.